Perceived professional roles and implications for clinical decision‐making. (1st October 2019) - Yu, Bonnie; Ghoneim, Abdulrahman; Lawrence, Herenia; Glogauer, Michael; Quiñonez, Carlos
Abstract: Objectives: This study aims to (a) investigate the relationship between dentists' perceived professional role (PPR), defined as the belief that they are health care professionals versus business people, and treatment intensity, determined by the aggressiveness of clinical approaches, such as in number or scope, and (b) identify the demographic and practice characteristics that have a relationship to PPR. Methods: A 46‐item survey with questions on dentists' demographic and professional characteristics was mailed to a random sample of 3, 201 general dentists in Ontario, Canada. PPR was measured by visual analog scale and by Likert‐type scale questions, which have been validated in the literature in terms of their ability to measure PPR. Treatment intensity was measured by a set of case scenarios. Univariate, bivariate, and multivariable analyses were performed. Results: One‐thousand and seventy‐five dentists returned usable surveys (33.6% response rate). When using the two methods to measure PPR, visual analog scale and Likert‐type scale questions, dentists who identified as business people tended to have a higher treatment intensity compared to those who identified as health care professionals ( p  < 0.1 and p  < 0.05, respectively). In multivariable logistic regression, years of practice, number of technologies used in a practice, and perceiving other dentists as competitors rather than colleagues were significant predictors of identifying as a business person. Conclusions: Dentists' PPRs had a significant relationship to the aggressiveness of treatment decisions. Demographic and practice characteristics also had significant relationships to PPR. These findings may have implications for public trust and dentistry's status as a health care profession.